PELATIHAN VIDEO RECORDING DAN EDITING VIDEO PADA SMK SWASTA GELORA JAYA NUSANTARA MEDAN - Gortap Lumbantoruan; Marlyna Infryanty Hutapea; Jamaluddin Jamaluddin; Emma Rosinta Simarmata; Eviyanti Novita Purba; Eva Julia Gunawati Harianja; Resianta Perangin-angin; Rimbun Siringoringo; Moris Raichel Sitanggang; Jonathan H. Saragih; Jujur Marentha Nababan (Universitas Methodist Indonesia, 2021)
The purpose of community service activities is to implement the “Tri Dharma” of Higher Education as well as to contribute ideas and transfer technology to teaching staff at SMK Gelora Jaya Nusantara Medan. This service activity was carried out for 2 days, with Video Recording and Video Editing Training materials. The topics given in this training are making video editing media and online learning content. The material given is the use of Filmora X software in video editing, and video recording techniques. This topic is very much needed in order to equip teachers in preparing and delivering subject matter during this COVID-19 pandemic. This topic was deliberately chosen considering that currently teachers are having difficulties in delivering subject matter face-to-face.